Monitoring Role of the Board and Ownership Concentration: From Interests Misalignment to Expropriation - Bozec, Richard; Dia, Mohamed (Université d'Ottawa | University of Ottawa, 2014)
Board independence is considered as a key corporate governance mechanism to help preserve the necessary checks and balances between the board and executive management. Despite all the value placed on the independent director by financial market participants and regulators, empirical evidence on the relation between board independence and firm performance is largely inconclusive. The objective of this paper is to revisit the board independence-performance relationship while taking into account the ownership structure of the firm. Two effects are unfolding along the ownership concentration spectrum: separation of ownership and control (Principal-Agent problems) and separation of voting and cash flow rights (Principal-Principal problems). The study is conducted over a four-year period (2002-2005) using panel regressions on a sample of Canadian publicly traded companies (502 firm-year observations). The results show a positive and significant relationship between board independence and Tobin’s Q only when ownership is concentrated in the hands of a controlling shareholder (legal control). The highest level of separation between voting and cash flow rights is also found in controlled entities. The higher the gap between voting and cash flow rights, the stronger the relationship between board independence and performance. Overall, evidence supports the expropriation effect argument. The findings underline the importance of putting in place independent directors in countries like Canada characterized by high ownership concentration and high levels of private benefits of control.
Le texte intégral de ce document de travail n''est pas disponible en ligne. Pour plus de renseignements sur ce document, veuillez communiquer avec la Direction de la recherche de l''École de gestion Telfer. The full text of this working paper is not available online. For more information regarding this working paper, please contact the Telfer School of Management Research Office.